2006
DOI: 10.1021/ie060138b
|View full text |Cite
|
Sign up to set email alerts
|

Desalination of Brackish Waters Using Ion-Exchange Media

Abstract: An environmentally friendly method and materials study for desalinating inland brackish waters (i.e., coal bed methane produced waters) using a set of ion-exchange materials is presented. This desalination process effectively removes anions and cations in separate steps with minimal caustic waste generation. The anion-exchange material, hydrotalcite (HTC), exhibits an ion-exchange capacity (IEC) of ∼3 mequiv g-1. The cation-exchange material, an amorphous aluminosilicate permutite-like material, (Na x +2 y A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The SPFT test was used to measure HTC uptake of silica under more rapid flow-through conditions and to provide a measure of uptake capacity. [15] Recall that the fluid residence time in the SPFT is ~ 7 minutes; batch reaction times were carried out to 25 hours. Greater than >90% silica removal occurs rapidly and persists until ~4 hours, at which point the rate of silica removal declines (see Figure 5).…”
Section: Single Path Flow Through (Spft) Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…The SPFT test was used to measure HTC uptake of silica under more rapid flow-through conditions and to provide a measure of uptake capacity. [15] Recall that the fluid residence time in the SPFT is ~ 7 minutes; batch reaction times were carried out to 25 hours. Greater than >90% silica removal occurs rapidly and persists until ~4 hours, at which point the rate of silica removal declines (see Figure 5).…”
Section: Single Path Flow Through (Spft) Measurementmentioning
confidence: 99%
“…[12][13][14] In an effort to develop highly selective silica ion-exchange materials that are robust, and both cost and energy efficient, we are exploring inorganic anion exchangers like hydrotalcites (HTC) as silica adsorbents. [15] HTCs are layered double-hydroxides with…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion exchange resins have also been used frequently in industry for wastewater treatment (Battaerd et al 1973;Abdulgader et al 2013). Documented studies reported that ion exchange technologies have the capability of treating fairly concentrated brackish water (Pless et al 2006;Smith and Sengupta 2015). The advantages of ion exchange treatment is that high pumping pressures, extensive pretreatment or high thermal energy input is not required.…”
Section: Introductionmentioning
confidence: 99%
“…The advantages of ion exchange treatment is that high pumping pressures, extensive pretreatment or high thermal energy input is not required. However, the process is limited by the saturation of the resin which needs large volumes of acidic and/or basic solutions for their regeneration (Hendry 1982;Pless et al 2006;Sarkar and SenGupta, 2007).…”
Section: Introductionmentioning
confidence: 99%